POVERTY REDUCTION IN ISLAMIC POLITICAL ECONOMIC ACCORDING TO ABDURRAHMAN AL-MALIKI'S PERSPECTIVE - Nunung Nurlaela (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2022)
This study aims to provide ideas in an effort to reduce poverty by using the thoughts of Abdurrahman al-Maliki. The sociological approach was chosen by studying literature derived from the work of 'Abdurrahman al-Maliki on as-Siyasah al-Iqtiṣadi al-Muṡla (Great Economic Politics). The results of the study provide new ideas for poverty alleviation, namely the complete fulfillment of the basic needs of each individual people and provide freedom of business to fulfill complementary needs in accordance with the Shari'a. The role of the state as the person in charge of the welfare of all citizens is a key factor in eradicating poverty, accompanied by creating job opportunities in the agricultural and trade sectors and building the industrial sector to meet market needs. Abstrak Penelitian ini bertujuan memberikan gagasan dalam upaya mengurangi kemiskinan dengan menggunakan pemikiran Abdurrahman al-Maliki. Pendekatan sosiologis dipilih dengan studi literatur berasal dari karya Abdurrahman al-Maliki mengenai as-Siyasah al-Iqtiṣadi al-Muṡla (Politik Ekonomi Besar). Hasil penelitian memberikan gagasan baru pengentasan kemiskinan, yaitu pemenuhan menyeluruh atas kebutuhan pokok setiap individu rakyat serta memberikan kebebasan berusaha untuk pemenuhan kebutuhan-kebutuhan pelengkapnya sesuai dengan syariat. Peran negara sebagai penanggung jawab kesejahteraan semua warga negara merupakan faktor kunci penghapusan kemiskinan, disertai dengan membuka lapangan pekerjaan dalam sektor pertanian dan perdagangan serta membangun sektor industri untuk memenuhi kebutuhan pasar.